Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1016/s0896-6273(00)80832-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Processing of Objects under Various Viewing Conditions in the Human Lateral Occipital Complex

Abstract: The invariant properties of human cortical neurons cannot be studied directly by fMRI due to its limited spatial resolution. Here, we circumvented this limitation by using fMR adaptation, namely, reduction of the fMR signal due to repeated presentation of identical images. Object-selective regions (lateral occipital complex [LOC]) showed a monotonic signal decrease as repetition frequency increased. The invariant properties of fMR adaptation were studied by presenting the same object in different viewing condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

128
813
7
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 1,097 publications
(955 citation statements)
references
References 49 publications
128
813
7
2
Order By: Relevance
“…In contrast, activations of face-selective regions in the STS do not correlate with recognition performance [11]. Sixth, the FFA rapidly habituates to repeated presentation of a face, suggesting that it is involved in fine-grain processing of faces, not just category detection [12,134]. Seventh, the FFA is activated more by face identity than variations in eye gaze or expression [9,12], while the STS showed the opposite effects [9].…”
Section: Neural Substrates Of Identity Recognition In Healthy Adults:mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, activations of face-selective regions in the STS do not correlate with recognition performance [11]. Sixth, the FFA rapidly habituates to repeated presentation of a face, suggesting that it is involved in fine-grain processing of faces, not just category detection [12,134]. Seventh, the FFA is activated more by face identity than variations in eye gaze or expression [9,12], while the STS showed the opposite effects [9].…”
Section: Neural Substrates Of Identity Recognition In Healthy Adults:mentioning
confidence: 97%
“…Here, we focus on a face selective region in the fusiform gyrus, namely the ''fusiform face area'' (FFA) [7] which has received particular attention for its role in face recognition in adults for several reasons. First, some patients who have suffered focal injury to the temporal cortex are selectively impaired in face recognition (prosopagnosia), while others are selectively impaired in the recognition of non-face objects (object agnosia) [133][134][135]. Second, neuroimaging methods have revealedspecific face-selective regions in the fusiform gyrus, namely the ''FFA'' [7].…”
Section: Neural Substrates Of Identity Recognition In Healthy Adults:mentioning
confidence: 99%
“…Studies using fMRI adaptation 5,20 have indicated that the FFA discriminates between different individual faces 36 and the LOC discriminates between individual object exemplars 37,38 . Adaptation studies have also shown that these regions are partly insensitive to size, position and spatial scale 39,40 but more sensitive to viewpoint and direction of illumination 37,41,42 .…”
Section: Box 1 | Recent Advances Through Functional Mrimentioning
confidence: 99%
“…In addition, fMRI adaptation has revealed sensitivity to a range of within-category differences 37,38,44 . In addition, category membership seems to be the main determinant of the population response in the IT.…”
Section: Box 1 | Recent Advances Through Functional Mrimentioning
confidence: 99%
See 1 more Smart Citation